Optimalisasi Potensi Pajak Pertambangan Mineral Bukan Logam dan Batuan (MBLB) dengan UU Hubungan Keuangan Pusat dan Daerah (HKPD) di Kabupaten Sukabumi - Rinaldi, Rinaldi; Ismatullah, Ismet (PT. Alahyan Publisher Sukabumi, 2024)
This research was conducted to try to provide a strategy on how to optimize the potensial for non metallic mineral and rock mining taxes (MBLB) in Sukabumi. This type of research uses quantitative methods with a descriptive approach and analyzis the optimization of the potential for non metallic mineral and rock mining taxes (MBLB), especially in relation to increasing Regional Original Income (PAD).Optimizing regional income by taxing non metallic minerals and rock can be done by taking an inventory of the numbers of miners, both companies and individuals, who already have a mining business permit (IUP) and thos who do not, monitoring the amount of production produced by the miners, accurate assessment of potential taxes imposed, taxe rate policies determined, regional taxes management. Trend analysis show and increase in tax realization for coming years, where this trend analysis is used to predict future condition. It is hoped that the results of this research can provide input to related parties, in the sukabumi district government efforts to optimize the potential for non metallic mineral and rock mining taxes (MBLB).